Effect of Heat Treatment (Ferritizing) on Chemical Composition, Microstructure, Physical Properties and Corrosion Behaviour of Spheroidal Ductile Cast Iron - ISMAEEL, A.R.; ABDEL REHIM, S.S.; ABDOU, A.E. (Asian Journal of Chemistry, 2010)
Two steps ferritizing technique was applied on ductile cast iron samples by austenitizing at 900ºC, air cooling to produce pearlite, ferritizing by reheating samples for different times at 700ºC and air cooling to room temperature. Chemical analysis and microstructure showed that as ferritizing time increased, an increase of percentage of ferrite, decrease of pearlite, with corresponding decrease in cementite and increase of free carbon in the form of spheroidal graphite. These changes explain the changes of physical (mechanical) properties represented in the increase of percentage elongation, decrease of tensile strength and decrease in brinle hardness. Weight loss corrosion test technique was followed for investigation of corrosion rate of heat treated samples in 0.1 N H2SO4 solution, which show decrease in corrosion rate with increased ferritizing time. This was explained due to decrease of cathodic sites represented in cementite forming pearlitic lamella. The exception was in the early step of ferritizing, where the corrosion rate increased due to formation of secondary graphite acting as effective cathodic sites.